Effects of Utilization of Maternal Health Care Services on Child Spacing: A Study from Eastern Nepal - Paudel, Ishwari Sharma; Gautam, Rabin (Journal of College of Medical Sciences-Nepal, 2015)
Objective: This study was conducted to explore the effect of utilization of Antenatal Care Service on subsequent birth interval. Methods: A cross-sectional study was conducted among 517 women giving birth during five years period preceding survey. The Cox proportional hazard model was used to analyze birth interval as a multivariate life table model. Results: ANC utilization was higher among mothers living in mountain, Indo-Aryan high caste and mothers having more than 10 years of schooling. Regression analysis showed that being Tibeto-Mongoloid caste, mothers with female index child and mother with dead index child had higher risk of having next birth. Conclusion: There is a strong positive relationship between the utilization of ANC service and less risk of child bearing. (RR=1.873, p = 0.008) JCMS Nepal 2014; 10(4):22-25